A revisit to the region of Collinder 132 using Carte du Ciel and Astrographic Catalogue plates - Orellana, Rosa Beatriz (2010)
Aims. Based on stellar positions and proper motions, we aim to re-analyse the region of the controversial open cluster Collinder 132. Methods. We have developed a model which analyses the proper motion distribution and the stellar density to find moving groups. The astrometric data were obtained from four Carte du Ciel (CdC) and one Astrogaphic Catalogue (AC) plates of the Córdoba Astronomical Observatory collection (Argentina). Results. We detected an open cluster from the field stars and calculated the mean proper motion and the membership probabilities of the region's stars. We report new coordinates of its centre αc = 108\fdg347, δc = -31\fdg011, the components of mean proper motion μ αcosδ = -2.62±0.44 mas/yr, μδ = 4.79±0.88 mas/yr. Thirteen stars are astrometric members giving a value of 20' for the cluster angular diameter. Six stars fulfil the astrometric and photometric criteria for being cluster members and locate the cluster at 360 pc from the Sun. We propose a simple model for the analysis of the proper motion distribution of an association. We report the components of the association mean proper motion μαcosδ = -1.38±0.14 mas/yr, μδ = 2.26±0.16 mas/yr. We found 149 astrometric members, 11 of which have reliable photometric data that locate them betweeen 417 and 660 pc from the Sun.